Community structure and spatial distribution of benthic fauna in the Bellingshausen Sea (West Antarctica). - Saiz, J.I.; García, F.J.; Manjón-Cabeza, Maria Eugenia; Parapar, J.; Peña-Cantero, A.; Saucède, Thomas; Troncoso, J.S.; Ramos, A. (Polar Biology, 2008)
9 pages International audience The structure and spatial distribution of the macrofauna community of the Bellingshausen Sea in the western sector of Antarctica was studied during the ‘BENTART–06' oceanographic expedition. This is one of the least explored Antarctic seas. A total of 20 box cores were sampled at 11 stations ranging from 157 to 3,304 m depth, using an USNEL-type box corer (BC) dredge. Representatives of 25 higher taxa of invertebrates were collected. Deeper sampling sites were less rich in taxa (4–7 taxa), whereas the Wgures were higher at shallower sites (up to 17 taxa). Faunal density on the sea bottom revealed a horizontal spatial gradient from the western sites with extremely low Wgures (90 indiv./m2) towards the eastern ones with the highest Wgures (1,360 indiv./m2) close to the Antarctic Peninsula. Several abiotic factors (depth, redox, organic matter, carbonates and particle size of surWcial sediments) were measured simultaneously on the sea Xoor to characterise the substrate preferences of the fauna. Positive correlations were found between the faunal distribution and a combination of depth, redox values, and organic matter content of sediments. This indicates decreasing availability of food in the deeper bottoms of the Bellingshausen Sea with a prevalence of depauperated bottoms dominated almost exclusively by a foraminiferans community.